Inflation and Inflation Uncertainty Nexus: Empirical Evidence from Pakistan - Sajid Amin Javed; Saud Ahmed Khan; Azad Haider; Farzana Shaheen (International Journal of Economics and Financial Issues, 2012)
This study examines relationship between Inflation and Inflation uncertainty for Pakistan using monthly data over 1957:1-2007:12. ARMA-GARCH model is applied to estimate conditional volatility of inflation. Findings of the study support Friedman-Ball hypothesis for Pakistan as Granger-causality test reveals that inflation affects inflation uncertainty positively. We find no evidence for inflation uncertainty affecting inflation rates as suggested by Cukierman & Meltzer (1986) and only unidirectional relation is evident with causality running from inflation to inflation uncertainty. High volatility persistence for inflation is also confirmed. Results of the study may be useful for policymakers at central bank to devise more efficient monetary policy.